Evaluating the biological quality of mass-reared Anopheles arabiensis males irradiated as pupae or as adults - Samar Eisa; Nonhlanhla Lindiwe Ntoyi; Bénéwendé Aristide Kaboré; Davor Skaric; Chantel Janet de Beer; Wadaka Mamai; Odet Bueno; Thomas Wallner; Simran Singh Kolta; Hanano Yamada (Malaria Journal)
Abstract Background The success of a sterile insect technique programme to control target mosquito populations depends on producing high-quality sterile males that can compete with wild males to inseminate wild females, to consequently inhibit procreation. To succeed, the released males require high biological quality. The quality of laboratory-reared, sterile males can be affected by the rearing conditions, handling, transportation, and irradiation. Limiting the cumulative damage caused by all these processes is key to maintain sterile male performance in the field once released. The ideal life stage to irradiate Anopheles arabiensis males is still an important question for this species. This study aims to assess the dose response of irradiated males at pupal versus adult stages and use quality control (QC) parameters to assess the feasibility and possible advantages of shifting to adult irradiation in this species. Methods Laboratory reared An. arabiensis males were irradiated as late-stage pupae or as adults at varying doses to compare the radiosensitivity in both developmental stages. Males irradiated at fully sterilizing doses were further subjected to quality control tests to compare the quality of males irradiated at adult versus pupae stages. The QC parameters tested included flight ability, longevity and mating competitiveness. Results The results show that adults do not require more radiation dose to achieve the target sterility, and females are more radiosensitive than males. Longevity, flight ability and mating competitiveness were improved significantly in males irradiated as adults compared to that of males irradiated as pupae. Conclusions Given the challenges in synchronizing pupation in a mass rearing setting and achieving a homogenous age (i.e. late-stage pupae) of collected pupae in this species, as well as these findings on the overall improvement of sterile male quality in the males irradiated as adults, this report provides a strong argument for irradiation protocols to shift towards adult stage irradiation in SIT programmes against An. arabiensis.